Students' Errors in Solving PISA-Based Mathematical Problems Viewed from Cognitive Style - Rum, Ahbi Mahdianing (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Students’ mathematical literacy is influenced by cognitive style which refers to individual variations in processing different subcomponents for the three main categories of cognitive processes which is perception, memory, and cognition. The difference of students’ characteristic in processing the information affects how they solve the question. This study aims to identify students' errors in solving PISA-based mathematical problems based on Newman's theory. This study used case study method which was carried out in one of the junior high schools in North Bengkulu Regency, Bengkulu Province, involving 32 students of class 8th in the 2022/2023 academic year who had studied number pattern. The subjects in this research were chosen purposively, there were 3 Field Dependent (FD) students namely LFD, MFD, and HFD. Data in the research were collected using the Group Embedded Figure Test, mathematical literacy tests which is developed according PISA-based level, and interviews. The result showed that when solving problems, earlier stage of error affected another error which led to a incorrect sollution. According to newman errors, the dominant errors experienced by LFD student when solving mathematical literacy problems were comprehension errors, process skill errors, and encoding errors. The dominant errors experienced by MFD students were transformation errors and encoding errors. Furthermore, the dominant errors experienced by HFD students were comprehension errors and transformation errors.